In vivo cytokine gene transfer by gene gun reduces tumor growth in mice. - Sun, W H (1995)
Implantation of tumor cells modified by in vitro cytokine gene transfer has been shown by many investigators to result in potent in vivo antitumor activities in mice. Here we describe an approach to tumor immunotherapy utilizing direct transfection of cytokine genes into tumor-bearing animals by particle-mediated gene transfer. In vivo transfection of the human interleukin 6 gene into the tumor site reduced methylcholanthrene-induced fibrosarcoma growth, and a combination of murine tumor necrosis factor alpha and interferon gamma genes inhibited growth of a renal carcinoma tumor model (Renca). In addition, treatment with murine interleukin 2 and interferon gamma genes prolonged the survival of Renca tumor-bearing mice and resulted in tumor eradication in 25% of the test animals. Transgene expression was demonstrated in treated tissues by ELISA and immunohistochemical analysis. Significant serum levels of interleukin 6 and interferon gamma were detected, demonstrating effective secretion of transgenic proteins from treated skin into the bloodstream. This in vivo cytokine gene therapy approach provides a system for evaluating the antitumor properties of various cytokines in different tumor models and has potential utility for human cancer gene therapy.